(3eHGOF GdGbJUGO Gdcdjs - (3EjeGf(B, (3YWjI fGUas ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2008)
(3ebOeGJ CSGSjI aj bjGS eSJhi GdfTGW GdGbJUGOj eY GdMSGHGJ GdbhejI h feGPL GdJOab GdOGFQj ddONd Gdbhej , GdWdH Gdcdj h eMOOGJg (B: (3GdGSJgdGc , GdGSJKeGQ , GdWdH GdMchej h GdWdH GdNGQLj eY GdJWQb Gdi JMOjO JhGRf GdONd Gdbhej aj GbJUGO eZdb HOhf McheI h GbJUGO eaJhM eY hLhO McheI , hcPdc GdfbhO h GdHfhc h eTcdI GdJVNe h GdHWGdI h YLR GdehGRfI GdYGeI aj GdGbJUGO Gdcdj h GNjQG GgejI GdJLGQI GdNGQLjI h GdSjGSI GdJOGQjI , ejRGf GdeOahYGJ h Shb GdUQa GdGLfHj(B.s
Keywords: (3GdGbJUGOs; (3GdGbJUGO Gdcdjs; (3GdONd Gdbhejs